Circular Economy-based Food Technology: Enhancing Red Dragon Fruit Jam Quality according to SNI 3746-2008 - Fia Lestari, Mega; Ismail, Nur Afia; Khaerunnisa, Munira; Nur Amri, Azhari; Nur Fuady, Muhammad Ikram; Utami, Hermin Hardyanti; Yusriadi, Yusriadi (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2023)
Circular economy-based food technology innovation plays important role in overcoming environmental and sustainability challenges. This study aims to improve the quality of red dragon fruit (Hylocereus polyrhizus) jam by adding its peel, in line with SNI 3746-2008. The study will also explore the application of circular economy principles in the jam production process. This research uses both quantitative and qualitative methods, including Total Plate Count tests, organoleptic tests (condition and hedonic), fibre tests, moisture content tests, and literature reviews. The research results show that the addition of red dragon fruit peel improves the quality of the jam, with a Total Plate Count that meets standards, making it safe for consumption at 3.6x10² Colony/g. Three parameters typically state the organoleptic acceptance level for condition tests as normal: colour (97%), odor (65%), and taste (74%). The hedonic test showed that the panelists liked the colour of the jam (7) and somewhat liked the odor and taste of the jam (6). The addition of red dragon fruit peel confirmed the positive fibre content. However, the panelists slightly disliked the jam's texture (4) due to its high moisture content (48.6%), indicating the need for improvement. From a circular economy perspective, this contributes to reducing biomass waste, utilising resources efficiently, increasing the added value of products, and providing a positive social and economic impact. This research's limitations include variations in raw material formulation that affect the final results, as well as the need for further studies to optimise moisture content and improve organoleptic test results.